2014
DOI: 10.1097/mph.0000000000000037
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic Production of β-hCG by Osteosarcoma

Abstract: Ectopic production of β-human chorionic gonadotropin (β-hCG) by nontrophoblastic tumors has been reported but mostly in carcinomas. We report a case of an adolescent female patient with a epithelioid osteosarcoma that was discovered to secrete β-hCG after routine pregnancy testing. Immunohistochemical staining of her primary tumor biopsy demonstrated immunoreactivity for β-hCG. Levels of serum β-hCG were monitored throughout her therapy and demonstrated normalization with effective systemic therapy and local c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 9 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…Leidinger et al reported positive staining in dedifferentiated metastases of negatively staining primary tumors [ 6 ], and Masrouha et al reported that four of the five cases stained positively in histologically high-grade tumors [ 5 ]. However, Oshrine et al reported no morphological differences between β -hCG-positive and β -hCG-negative cells within the same tumor [ 7 ]. In our case, the tumor appeared of low-grade and, similar to Orhrine's findings, no noticeable differences were seen between β -hCG-positive and β -hCG-negative areas.…”
Section: Discussionmentioning
confidence: 99%
“…Leidinger et al reported positive staining in dedifferentiated metastases of negatively staining primary tumors [ 6 ], and Masrouha et al reported that four of the five cases stained positively in histologically high-grade tumors [ 5 ]. However, Oshrine et al reported no morphological differences between β -hCG-positive and β -hCG-negative cells within the same tumor [ 7 ]. In our case, the tumor appeared of low-grade and, similar to Orhrine's findings, no noticeable differences were seen between β -hCG-positive and β -hCG-negative areas.…”
Section: Discussionmentioning
confidence: 99%
“…Workup and treatment of the femoral lesion revealed a high-grade osteosarcoma which stained positive for β-hCG. Oshrine et al 8 in 2014 also reported a case of osteosarcoma in an adolescent female which was secreting β-hCG. Serum β-hCG levels became undetectable by the end of her sarcoma treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In the available literature, there are a few documented cases of β-hCG-producing sarcomas. β-hCG production was described in a small number of primary and recurrent osteosarcomas and osteogenic sarcomas [11][12][13][14][15], phyllodes tumors [16], dedifferentiated liposarcomas [17,18] and synovial sarcomas [19]. In extra-uterine cases, elevated β-hCG was described in retroperitoneal leiomyosarcoma [18,20,21], spermatic cord leiomyosarcoma [22,23], and leiomyosarcoma of the small bowel [24].…”
Section: Discussionmentioning
confidence: 99%